The final twist [large type] - Deaver, Jeffery (Deaver, Jeffery. Colter Shaw series., 2021)
"Colter Shaw finds himself in San Francisco, where he has taken on the mission his father began years ago: locating a missing courier bag containing evidence that will bring down a corporate espionage firm responsible for hundreds, perhaps thousands, of deaths. Following the enigmatic clues his father left behind, Shaw plays cat and mouse with the company's sadistic enforcers. Only by finding the courier bag can he expose the company and stop the murder of an entire family--slated to die in forty-eight hours. With the help of an unexpected figure from his past, Shaw narrows in on the truth"--Page 4 of cover.